The Effect of the Make-A-Match Cooperative Learning Model with Wordwall Educational Game on Fifth-Grade the Science Learning Outcomes: Indonesia - Kadek Helin Dwi Sartika; Ni Wayan Rati; I Kadek Suartama (Mimbar Pendidikan Indonesia, 2025)
Learning Science and Social Sciences (IPAS) in elementary schools is still dominated by the lecture method which causes low learner involvement and learning outcomes that are not optimal. A more interactive and technology-based learning model needs to be applied to improve the effectiveness of learning. This study aims to analyze the effect of Make a Match learning model assisted by Wordwall on students' IPAS learning outcomes. This study used a pseudo-experimental method with a non-equivalent post-test only control group design. The research sample consisted of 49 students. Data were collected using multiple choice objective tests to measure learning outcomes. Data analysis techniques include descriptive statistics and t-test to determine significant differences between the two groups. The results showed that the use of Make a Match model assisted by Wordwall significantly improved students' learning outcomes compared to conventional methods. The conclusion of this study is that the Make a Match model assisted by Wordwall can be an innovative alternative in increasing the effectiveness of IPAS learning. The implication of this research is the need for teachers to apply more interactive technology-based learning strategies to improve students' concept understanding and learning motivation.